1995
DOI: 10.1095/biolreprod53.4.749
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Testicular Responses to Exogenous Growth Hormone and Follicle-Stimulating Hormone in Prepubertal Boars1

Abstract: The effects of exogenous growth hormone (GH) and FSH on development of the testes in intact prepubertal boars was investigated. Twenty-four boars received one of four daily treatments from 8 through 40 days of age: 1) 90 micrograms porcine (p) GH/kg body weight (BW), 2) 100 micrograms pFSH/kg BW, 3) GH + FSH, or 4) vehicle only (control). Plasma testosterone levels, measured at 10-day intervals, were similar among groups of boars throughout the study. Body weights among groups were similar during treatment, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 51 publications
4
20
0
2
Order By: Relevance
“…Exogenous GH and follicle-stimulating hormone have been shown to influence testicular maturation (Swanlund et al 1995). Graft development appeared to be sufficiently supported by endogenous mouse gonadotropins.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Exogenous GH and follicle-stimulating hormone have been shown to influence testicular maturation (Swanlund et al 1995). Graft development appeared to be sufficiently supported by endogenous mouse gonadotropins.…”
Section: Discussionmentioning
confidence: 96%
“…Graft development appeared to be sufficiently supported by endogenous mouse gonadotropins. GH is elevated around puberty and is associated with compensatory testicular hypertrophy and early onset of spermatogenesis after neonatal hemicastration (Kosco et al 1987, al Haboby et al 1988, Swanlund et al 1995. To test whether hormonal supplementation of recipient mice with bovine GH could improve spermatogenic efficiency, recipient mice were treated with exogenous bovine GH.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that Sertoli cells provide the environment that protects and nourishes germ cells and supports their development to viable sperm (França and Chiarini-Garcia, 2005) and Sertoli cell proliferation in pigs begins during the prenatal period (McCoard et al, 2002) and continues after birth (Swanlund et al, 1995;França et al, 2000). A critical period of Sertoli cell proliferation occurs during the first 3 weeks after birth (McCoard et al, 2003) and the total number of Sertoli cells achieved will determine testicle size in adulthood, as well as the sperm production capacity (Cooke et al, 1992;Hess et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The GH-deficient dwarf mouse has reduced testicular weight, seminiferous tubular diameter and germ cell number; however, with GH administration during the postnatal period these parameters can be normalised (5). In the prepubertal boar exogenous GH increased Sertoli cell size, tubular lumen formation and initiated spermatogenesis earlier than in controls (6). Reduced seminal fluid volume and total sperm number/ ejaculate compared with reference groups were found in patients with isolated GH deficiency (7).…”
Section: Introductionmentioning
confidence: 99%